2017
DOI: 10.1123/ijspp.2016-0433
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Changes in Acute Training Load on Daily Sensitivity of Morning-Measured Fatigue Variables in Elite Soccer Players

Abstract: Purpose:To determine the sensitivity of a range of potential fatigue measures to daily training load accumulated over the previous 2, 3, and 4 d during a short in-season competitive period in elite senior soccer players (N = 10). Methods: Total highspeed-running distance, perceived ratings of wellness (fatigue, muscle soreness, sleep quality), countermovement-jump height (CMJ), submaximal heart rate (HRex), postexercise heart-rate recovery (HRR), and heart-rate variability (HRV: Ln rMSSD) were analyzed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 49 publications
2
107
3
3
Order By: Relevance
“…In the third study, perceived ratings of fatigue were significantly correlated to short-term load accumulation (1–4 days), respectively 5. These findings demonstrate that athlete self-report measures, particularly perceived fatigue was significantly sensitive to daily and short-term training load accumulation.…”
Section: What Did I Find? Overview Of Main Findingsmentioning
confidence: 51%
“…In the third study, perceived ratings of fatigue were significantly correlated to short-term load accumulation (1–4 days), respectively 5. These findings demonstrate that athlete self-report measures, particularly perceived fatigue was significantly sensitive to daily and short-term training load accumulation.…”
Section: What Did I Find? Overview Of Main Findingsmentioning
confidence: 51%
“…Such research has shown that athletes are liable to suffer reduced sleep quantity and quality (16,22,32), which can lead to decrements in sporting performance (7,23), increased risk of illness (6) and deviations in wellbeing measures (19,27). These findings have resulted in practitioners commonly including measures of perceived sleep quality in daily wellbeing questionnaires aimed at monitoring their athletes (2,24,40).…”
Section: Introductionmentioning
confidence: 99%
“…Daily wellbeing questionnaires usually consist of items related to muscle soreness, appetite, sleep quality, mood, stress and fatigue, and are tailored to the needs of the practitioners in question (24,26,40). These subscales can be evaluated alone or grouped together to provide a total wellbeing score, which can be compared to the previous day's training load to assess whether changes are congruent with the training stress imposed on the athlete (25,36,37,40). However, given the influence of sleep quality on athlete wellbeing (19,27,29), it is pertinent to question whether perceptions of sleep should be an input, rather than an output measure of this athlete monitoring process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practitioners need to accurately and efficiently monitor an individual athlete's fatigue (readiness to train) to potentially make informed and immediate adjustments to their TL. Various objective and subjective measures have been utilised to inform practitioner decision-making (Saw, Main, & Gastin, 2015); however, a "gold-standard" single or battery of measures is not adopted within general practice (Halson, 2014) or soccerspecific practice (Akenhead & Nassis, 2016;Thorpe et al, 2015Thorpe et al, , 2016aThorpe et al, , 2016b. Common methods employed are subjective questionnaires (Thorpe, Atkinson, Drust, & Gregson, 2017), visual analogue scales (Saw et al, 2015), blood and saliva indices (Ascensao et al, 2008;Morgans, Owen, Doran, Drust, & Morton, 2015;Thorpe & Sunderland, 2012), physical performance protocols and/or their physiological responses (Buchheit, 2014;Buchheit et al, 2013).…”
Section: Introductionmentioning
confidence: 99%